Pendapatan Usaha Pengolahan Hasil Perikanan (Kerupuk Atom Emi) Di Desa Malang Rapat Kabupaten Bintan - Mita, Mita; Hafsar, Khairul; Tetty, Tetty (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Universitas Maritim Raja Ali Haji, 2021)
The village of Malang Rapat is one of the areas with high enough fishery products, of course, it has enormous potential in developing fishery product processing businesses. In the village of Malang Rapat, there is a fishery product processing business, namely the Atomic Cracker Business. This study aims to analyze operating costs, income. This study aims to analyze operating costs, income, and breakeven points. The research method used is the description. Sampling was carried out by census, namely an Emi atomic cracker business. The types and sources of data used consist of primary data and secondary data. The results showed that the total cost of processing fishery products (Emi Atomic Crackers) in the village of Malang Rapat, Bintan Regency, was Rp357,559,100 per year. Was Rp357.559.100 per year. The income earned is Rp1.085.512.900 per year. Overall, the results of the calculation of fishery product processing business income (Emi Atomic Crackers) in the Village of Malang Rapat, Bintan Regency, generated considerable income during 2021 and could cover the costs incurred in the production process.